An Analysis of Regulation 363 of the National Health Act (61 of 2003) Regarding the Management of Human Remains from the Perspective of Emerging Funeral Directors - MAPHELA, BULELWA (African Journal of Governance and Development, 2023)
The National Health Act 2003 (Act 61 of 2003) was formulated for the purpose of providing a governing and regulatory framework for a structured, homogenous healthcare system within the Republic of South Africa. In 2013, with regards to section 68(1)(b) read with section 90(4)(c) of the National Health Act 2003 (Act 61 of 2003), the regulations pertaining to the management of human remains were gazetted. Chapter 3 of the regulations, which deals with “Funeral Undertakers’ Premises and Mortuaries”, is the focus of this paper. As emerging businesses, many emerging funeral directors (EFDs) are currently struggling to comply with the onerous regulations of human remains management, with many mortuary premises operating without a valid Certificate of Compliance (CoC). Members of the funeral industry undertook national strikes to voice these concerns and challenges. In March 2022, the National Health Department proposed a new version of the regulations. The government gazette (No. 46048) in which these regulations were published did not refer to Regulation 363 or its repeal and replacement, though this must be assumed because the document matches Regulation 363 in terms of layout and completeness, with only minor differences. This paper assessed if the proposed regulations were a response to the challenges experienced by the EFDs around current regulations. A parallel comparison of the old and newly proposed human remains regulations was conducted via a content analysis, to assess whether the proposed amendments could improve the sustainability of EFDs. The study found that the proposed regulation was more stringent than the current one. The struggling EFDs seem to have no chance of being compliant should this Regulation be tabled.